Búsqueda de correlaciones de rayos gamma con nuevas fuentes de radio astrofísicas - Best Reyes, Sergio André (2019)
In this work we study two newly discovered classes of radio sources: the highly energetic, short-lived events, known as Fast Radio Bursts (FRBs), and a new category of compact sources known as Fanaroff-Riley type 0 radio galaxies (FR0s). Due to a possible catastrophic event origin for the FRBs and a previous correlation found with an FR0 in the Γ-rays spectrum, it is possible that these radio sources could also emit high energy photons in the Fermi-LAT satellite energy range (20 MeV - 300 GeV). Here we present an exhaustive time-dependent and spatial search of all up-to-date observed FRBs and FR0s, respectively. We perform a likelihood analysis of the radio sources by modeling the excess flux of gamma rays with a varying index power law function using data from Fermi-LAT and the 3FGL catalog. No correlations with more than 5 σ were found. Two FRBs and one FR0 with more than 4 σ were further analyzed. However, the significance from these sources is most likely due to nearby blazars. Therefore, upper limits for all sources are calculated.